2013
DOI: 10.4236/abb.2013.410a3005
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of serotonergic gene expression in the raphe nuclei of the midbrain under positive fighting experience in male mice

Abstract: The concept of a major inhibitory role of serotonin in aggressive behavior is widely accepted by investigators. There was ample evidence that a pharmacologically-induced increase in the serotonin activity attenuates agonistic behavior in animals, and that the manipulations inhibiting the brain serotonergic system can elicit aggressiveness in male mice and rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
4
17
0
1
Order By: Relevance
“…We have previously conducted studies of gene expression in males in similar experiments using the RT-PCR method with larger samples for each compared experimental group, i.e., winners and losers (> 10 animals). The direction and extent of changes in expressions of the Tph2, Slc6a4, Bdnf, Creb1, and Gapdh genes in the midbrain raphe nuclei of males compared with the control produced by two methods, including RT-PCR [41,42] and RNA-Seq, are generally consistent. This finding suggests that the transcriptome analyses of the data provided by the Company Genoanalitika (http://genoanalytica.ru, Moscow) have been verified, and this method reflects the actual processes that occur in the brain under our experimental paradigm.…”
Section: Rna-seqmentioning
confidence: 68%
“…We have previously conducted studies of gene expression in males in similar experiments using the RT-PCR method with larger samples for each compared experimental group, i.e., winners and losers (> 10 animals). The direction and extent of changes in expressions of the Tph2, Slc6a4, Bdnf, Creb1, and Gapdh genes in the midbrain raphe nuclei of males compared with the control produced by two methods, including RT-PCR [41,42] and RNA-Seq, are generally consistent. This finding suggests that the transcriptome analyses of the data provided by the Company Genoanalitika (http://genoanalytica.ru, Moscow) have been verified, and this method reflects the actual processes that occur in the brain under our experimental paradigm.…”
Section: Rna-seqmentioning
confidence: 68%
“…We have previously conducted studies of gene expression in males in similar experiments using the RT-PCR method with larger number of samples for each compared experimental group, i.e., winners and losers (> 10 animals). The direction and extent of changes in expressions of the Tph2, Slc6a4, Bdnf, Creb1, and Gapdh genes in the midbrain raphe nuclei of males compared with the control produced by two methods, including RT-PCR [Smagin et al 2013;Boyarskikh et al 2013] and RNA-Seq , are generally consistent. In order to cross-validate the our results obtained, we employed the unique resource from Barres Lab, Stanford University, USA [Zhang et al 2014] and found highly concordant with our RNA-Seq data pool ].…”
Section: Rna-seqmentioning
confidence: 70%
“…The midbrain raphe nuclei contain the bodies of serotonergic neurons which are involved in the regulation of many physiological, behavioral, and emotional processes. Repeated experience of aggression and defeats is accompanied by the decrease of serotonergic activity [Kudryavtseva 2006;Avgustinovich et al 2004], which is accompanied by decreased expression of serotonergic genes -Tph2, Maoa, Slc6a4, Htr's Smagin et al 2013;Kudryavtseva et al 2017] in this brain region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations